Analogues of some Tauberian theorems for stretchings - Richard F. Patterson (International Journal of Mathematics and Mathematical Sciences)
We investigate the effect of four-dimensional matrix transformation on new classes of double sequences. Stretchings of a double sequence is defined, and this definition is used to present a four-dimensional analogue of D. Dawson's copy theorem for stretching of a double sequence. In addition, the multidimensional analogue of D. Dawson's copy theorem is used to characterize convergent double sequences using stretchings.